TOWARDS THE STUDENTS’ USE OF BACKCHANNEL SIGNALS WITHIN THE CONTEXT OF VIRTUAL (ZOOM) CLASS: THE STUDENTS’ PERSPECTIVE - Nebieridze, Mariam (Online Journal of Humanities ETAGTSU, 2023)
This paper deals with special signals which show the speaker that their message is getting through. These signals are examined in online classroom discourse, taking place via Zoom and emphasis is placed on students’ perspective in relation to the use of the abovementioned signals. The data were collected through questionnaires that have been prepared in Google Form to circulate among the undergraduate students from the Department of English Philology, Faculty of Humanities at Ivane Javakhishvili Tbilisi State University. After the thorough study of linguistic and empirical data, the frequency of the usage of backchannels by students has been established and the types of backchannel signals were distinguished. In addition, the students’ perspective on the function of the backchannel signals has been determined and Zoom-specific backchannel signals were identified. Full Text (PDF)